1996
DOI: 10.1093/jaoac/79.5.1124
|View full text |Cite
|
Sign up to set email alerts
|

Anatoxin B1 in Common Egyptian Foods

Abstract: Samples of common Egyptian foods (17 nuts and seeds, 10 spices, 31 herbs and medicinal plants, 12 dried vegetables, and 28 cereal grains) were collected from markets in Cairo and Giza. A portion of each sample was extracted with chloroform, and the concentrated extract was cleaned by passing through a silica gel column. Aflatoxin Bi was determined by reversed-phase liquid chromatography with UV detection. The highest prevalence of aflatoxin B1 was in nuts and seeds (82%), followed by spices (40%), herbs and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Previous studies developed by other authors found AFB 1 in liquorice root in a mean concentration that range from 170 to 590 µg kg −1 ,5, 13 and in rhubarb in a level of 48 µg kg −1 ,21 while in senna leaves, elder flower, lemon balm leaves no AFs contamination was found 22, 23. OTA has been found in samples of liquorice root with mean concentration 50 µg kg −1 ,13 or in a range of 0.3–252.8 µg kg −1 ,9, 24 but elder flower and lemon balm leaves were OTA negatives 22.…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies developed by other authors found AFB 1 in liquorice root in a mean concentration that range from 170 to 590 µg kg −1 ,5, 13 and in rhubarb in a level of 48 µg kg −1 ,21 while in senna leaves, elder flower, lemon balm leaves no AFs contamination was found 22, 23. OTA has been found in samples of liquorice root with mean concentration 50 µg kg −1 ,13 or in a range of 0.3–252.8 µg kg −1 ,9, 24 but elder flower and lemon balm leaves were OTA negatives 22.…”
Section: Resultsmentioning
confidence: 82%
“…India, Iran, Brazil, Turkey, and Egypt) were developing countries as defined by the United Nations, which suggests that each perceive this issue as a serious problem. Among this grouping, there was international diversity not associated [58,59], Iran [60], India [61][62][63][64], Brazil [51,65], and Egypt [66]) caused exceptionally large morbidity and mortality connected with such outbreaks [1,[67][68][69], and this may explain why more research has emphasized on aflatoxin since that time [28]. Analysis of international collaborations (i.e., link strength) showed that the United States had the highest number of collaborators (n = 87) followed by the United Kingdom (n = 63), and Italy (n = 54) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This study aims to assess 3 aflatoxin exposure in a selected group of nursing Egyptian mothers by measuring the level of 4 AFM 1 in breast milk. Aflatoxin exposure is known to occur in Egypt (El-Nezami et al 2000; 5 Hifnawy et al 2004;Selim et al 1996), though there is limited biomarker data from this region.…”
mentioning
confidence: 99%